Integrasi Dzikir Jahr La Ilaha Illallah Dalam Mengiringi Jenazah : Tinjauan Hadis Nabawi dan Perspektif Psikologi Kematian - Akhnaf, Muhammad; Muhammad Syaikhu; Muhammad Iqbal Ash-Shidqi; Amrullah (Jurnal Ilmiah Ilmu Ushuluddin, 2024)
Facing death for a Muslim often induces emotional turmoil that affects individual actions, particularly in the process of accompanying the deceased. The practice of reciting dzikir la ilaha illallah is frequently performed to soothe the heart. However, understanding the limitations and impacts of this practice is essential to ensure compliance with Islamic teachings. This study aims to examine the boundaries of reciting dzikir aloud during funeral rites and analyze the effects of dzikir la ilaha illallah on emotional reinforcement, spirituality, and the meaning of death. The research employs a qualitative method with content analysis and literature review approaches. Data were collected through literature searches related to funeral guidance and its psychological impacts. The findings indicate that reciting dzikir jahr la ilaha illallah during funerals is permissible within certain limits. This practice has proven to have a positive impact on enhancing emotional and spiritual aspects, as well as increasing awareness of the meaning of death as a life phase that needs preparation.